SEASONAL VARIATIONS OF BACTERIAL FLORA OF FRESH OIL SARDINES(Sardinella longiceps) - KARTHIAYANI, T C; IYER, K MAHADEVA (Fishery Technology, 2025)
An elaborate study was made on the qualitative and quantitative seasonal variations in the bacterial flora of fres.h oil sardines and their biochemical reactions. It was observed that the total bacterial loads and their phosphorescent and biochemical characters were influenced by changes in seasons. During monsoon season total bacterial count was high. Mesophiles predominated during summer, but phosphorescent bacteria were less. Winter favoured the selection of biochemically less active groups of bacteria.